1991
DOI: 10.1002/hep.1840130211
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor necrosis factor, interleukin-1 and interleukin-6 concentrations in chronic alcoholic patients

Abstract: Although altered cytokine homeostasis has been implicated in the pathogenesis of alcoholic liver disease, the relationship between cytokines and metabolic consequences of alcoholic liver disease is unknown. We, therefore, sought to correlate circulating concentrations of tumor necrosis factor-alpha, interleukin-1 and interleukin-6 to clinical and biochemical parameters of liver disease in chronic alcoholic patients. We used an enzyme-linked immunosorbent assay to measure plasma tumor necrosis factor and interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
240
0
7

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 518 publications
(260 citation statements)
references
References 43 publications
10
240
0
7
Order By: Relevance
“…18 In patients with various liver diseases, serum concentrations of proinflammatory cytokines TNF-␣, IL-1, and IL-6 are elevated. 19 The hepatic expression of the proinflammatory cytokines TGF-␤ 1 , TNF-␣, and IL-1␤ was recently shown by us to increase preferentially in the perivenous acinar liver region of rats treated chronically with ethanol, 17 which is in line with the early pathological changes seen in this part of the liver acinus.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…18 In patients with various liver diseases, serum concentrations of proinflammatory cytokines TNF-␣, IL-1, and IL-6 are elevated. 19 The hepatic expression of the proinflammatory cytokines TGF-␤ 1 , TNF-␣, and IL-1␤ was recently shown by us to increase preferentially in the perivenous acinar liver region of rats treated chronically with ethanol, 17 which is in line with the early pathological changes seen in this part of the liver acinus.…”
mentioning
confidence: 53%
“…Clinically, plasma TNF-␣ concentrations do not reflect improvement in liver disease, although it has some prospective value. 19,45 Most probably, in addition to down-regulation of proinflammatory cytokines, 36 the presumed development of tolerance to endotoxin also involves enhanced endotoxin binding and inactivation by albumin, high density lipoprotein, transferrin, and LBP 56,57 as well as by the reticuloendothelial system. 36,58 Furthermore, the different drinking patterns of the alcoholics may cause temporal variations in their endotoxin levels, which could modify the development of tolerance.…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…Derangements of receptor activator of NF-B (RANK), RANK ligand, and osteoprotegerin may also be involved in the pathogenesis of CUA because this system is involved in regulation of extraskeletal mineralization (42). Some of the factors that predispose to NUC (parathyroid hormone, corticosteroids, and liver disease) are known to increase the expression of RANK ligand and decrease the expression of osteoprotegerin, thus activating NF-B or degrading the inhibitory protein of NF-B (or a combination of these) (43)(44)(45). Warfarin may inhibit vitamin K-dependent carboxylation of matrix-Gla protein, decreasing the activity of the protein to inhibit calcification locally (46).…”
Section: Discussionmentioning
confidence: 99%
“…More than 20 years ago, we first reported that in patients with AH, basal and endotoxin-stimulated monocyte TNF production levels are increased. Subsequent studies showed that plasma and monocyte proinflammatory cytokines correlated with the clinical course of AH and survival [46,47]. Unfortunately, recent human studies have not demonstrated therapeutic efficacy for biologics such as anti-TNF antibody/TNF-soluble receptors in AH [48,49].…”
Section: Gut-liver Axis and Cytokine Signalingmentioning
confidence: 99%